Les pratiques de care par les pères après une naissance par césarienne : entre réajustements des normes de genre et (re)production d’inégalités - Ainhoa Sáenz Morales (Anthropologie & Santé)
After a cesarean, mothers are generally unable to take care of the newborn due to hospital protocols, their lack of mobility, the effects of the anesthesia, and postoperative pain. As a result, the father becomes a figure of care for the newborn. Research in social sciences on fathers’ experiences of caesarean is still scarce, although fathers are invited by medical staff to enter the operating theater in most countries, including Switzerland, where one in three births is a cesarean. Based on ethnographic fieldwork in two maternity units, this article documents the care practices performed by fathers, and explores how these practices reconfigure gender norms and simultaneously (re)produces class inequalities.